PENGARUH MEDIA PEMBELAJARAN WORDWALL TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Deni Okta Nadia; Desyandri (STKIP Subang, 2022)
In order to create a conducive learning environment and achieve maximum results, as educators, they must be aware and able to make updates in education. Using learning media that is effective, interesting, fun, and meaningful for students is one of the methods of learning renewal. In this case, wordwall learning media is used. This study aims to determine the influence of Wordwall learning media on the learning outcomes of elementary school students. This research method uses quasi-experimental design type Post-test only control group design. The subjects of this study were all grade V students of SDN 14 Simpangampek with a total of 40 people. The sampling technique in this study was saturated sampling with a total sample of 20 students as an experimental class and 20 students as a control class. The data collection technique in the form of a Post-test uses test questions in the form of multiple choices. The results showed that the use of wordwall learning media is superior to conventional learning or without involving learning media. Thus, it can be concluded that the use of wordwall learning media affects the learning outcomes of grade V students of SDN 14 Simpangampek. Keywords: Wordwall, Learning Outcomes, Elementary School